Reverse transcriptase inhibitors promote the remodelling of nuclear architecture and induce autophagy in prostate cancer cells. (28th May 2020) - Bellisai, Cristina; Sciamanna, Ilaria; Rovella, Paola; Giovannini, Daniela; Baranzini, Mirko; Pugliese, Giusj Monia; Zeya Ansari, Mohammad Salik; Milite, Ciro; Sinibaldi-Vallebona, Paola; Cirilli, Roberto; Sbardella, Gianluca; Pichierri, Pietro; et al.
Abstract: Emerging data indicate that the reverse transcriptase (RT) protein encoded by LINE-1 transposable elements is a promising cancer target. Nonnucleoside RT inhibitors, e.g. efavirenz (EFV) and SPV122.2, reduce proliferation and promote differentiation of cancer cells, concomitant with a global reprogramming of the transcription profile. Both inhibitors have therapeutic anticancer efficacy in animal models. Here we have sought to clarify the mechanisms of RT inhibitors in cancer cells. We report that exposure of PC3 metastatic prostate carcinoma cells to both RT inhibitors results in decreased proliferation, and concomitantly induces genome damage. This is associated with rearrangements of the nuclear architecture, particularly at peripheral chromatin, disruption of the nuclear lamina, and budding of micronuclei. These changes are reversible upon discontinuation of the RT-inhibitory treatment, with reconsititution of the lamina and resumption of the cancer cell original features. The use of pharmacological autophagy inhibitors proves that autophagy is largely responsible for the antiproliferative effect of RT inhibitors. These alterations are not induced in non-cancer cell lines exposed to RT inhibitors. These data provide novel insight in the molecular pathways targeted by RT inhibitors in cancer cells. Highlights: RT inhibitors inhibit cell proliferation and induce autophagy in prostate cancer cells, but not in non-cancer cells. RT inhibitory treatment induces DNA damage, increased intensity of H3K9me2 and fragmentation of the nuclear lamina. Concomitant with this nuclear reorganisation, cancer cells activate the autophagic pathway. These results confirm that RT inhibitors are anticancer agents and provide novel insight into their molecular mechanisms.